Pengaruh Pemikiran Ekonomi Al-Ghazali terhadap Pengembangan Ekonomi Syariah di Indonesia: Studi Kasus pada Lembaga Keuangan Syariah - Nurul Heria (CV Kalimasada Group, 2025)
The development of Islamic economics in Indonesia has shown significant growth over the last two decades, yet it still faces challenges in strengthening its foundational normative values. This study aims to analyze the influence of Al-Ghazālī's economic thought on the development of Islamic economics, specifically within the operational context of Islamic financial institutions in Indonesia. The research employs a qualitative method with a library research approach, examining scientific journals published within the last five to ten years to identify the relevance of Al-Ghazālī's concepts of maslahah, maqāṣid al-syarī‘ah, and economic ethics in modern institutional practices. The results indicate that Al-Ghazālī’s fundamental principles, particularly regarding maslahah, distributive justice, and the function of money exert a strong influence on policy formulation, product development, and the governance of Islamic financial institutions. Various journals also confirm that maqāṣid indicators are beginning to be utilized as performance evaluation instruments for Islamic financial institutions, although their application remains non-uniform. The study concludes that Al-Ghazālī’s thought remains relevant in supporting the strengthening of the national Islamic economic paradigm; however, its implementation requires enhanced institutional capacity and methodological standardization. These findings emphasize the importance of integrating classical values into contemporary Islamic economic practices to achieve goals that are more oriented toward public welfare (maslahah) and sustainability.